Long term performance of atomic layer deposition coatings for corrosion protection of stainless steel. Issue 9 (20th January 2015) - Marin, E.; Lanzutti, A.; Paussa, L.; Guzman, L.; Fedrizzi, L.
<x xml:space="preserve">Abstract</x> The use of atomic layer deposition (ALD) for the corrosion protection of metallic substrates was speculated for the first time in the 1990 s. Since then, a lot of research has been carried on to investigate the application limits of this technique. ALD has been efficiently used to deposit conformal oxide layers on different metallic substrates, which were used as insulators and diffusion barriers to prevent contact between aggressive electrolytes and metal. In this work, a complete morphological and compositional characterization of some ALD coatings has been carried out using atomic force microscopy and glow discharge optical emission spectrometry. Electrochemical impedance spectroscopy and potentiodynamic polarizations have been used to evaluate the over‐time performance of three different ALD deposits on AISI 316 stainless steel, namely TiO2, Al2O3 and AlN, and the results have been compared to previous literature data. It has been observed that, in contrast with the previous literature results, Al2O3 layers deposited on AISI 316 do not suffer premature failure. On the contrary, a lower and time‐dependent corrosion protection was observed when using TiO2 coatings and a decrease of corrosion protection over time due to oxidative phenomena of the protective layer has been observed in the case of the AlN coatings.